2020
DOI: 10.1101/2020.12.16.423040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conidial fusion in the asexual fungusVerticillium dahliae

Abstract: Cell-to-cell fusion is a fundamental biological process across the tree of life. In filamentous fungi, somatic fusion (or anastomosis) is required for the normal development of their syncytial hyphal networks, and it can initiate non-sexual genetic exchange processes, such as horizontal genetic transfer and the parasexual cycle. Although these could be important drivers of the evolution of asexual fungi, this remains a largely unexplored possibility due to the lack of suitable resources for their study in thes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Nevertheless, strains of F. oxysporum and V. dahliae harbor either the MAT1-1 or MAT1-2 versions of the MAT1 locus [57,58] and not both as is the case for homothallic species such as F. graminearum. The F. oxysporum strain in which chemotropism was studied carries the MAT1-1 version of the locus, while the V. dahliae strain studied carries the MAT1-2 version [15,59]. In the current study, we examined both MAT1-1 and MAT1-2 isolates in the sexual fungus F. circinatum and found that strains of either mating specificity responded chemotropically to synthetically produced α-peptide pheromone.…”
Section: Discussionmentioning
confidence: 88%
“…Nevertheless, strains of F. oxysporum and V. dahliae harbor either the MAT1-1 or MAT1-2 versions of the MAT1 locus [57,58] and not both as is the case for homothallic species such as F. graminearum. The F. oxysporum strain in which chemotropism was studied carries the MAT1-1 version of the locus, while the V. dahliae strain studied carries the MAT1-2 version [15,59]. In the current study, we examined both MAT1-1 and MAT1-2 isolates in the sexual fungus F. circinatum and found that strains of either mating specificity responded chemotropically to synthetically produced α-peptide pheromone.…”
Section: Discussionmentioning
confidence: 88%